2004
DOI: 10.1210/en.2003-1297
|View full text |Cite
|
Sign up to set email alerts
|

Human Placental Growth Hormone Increases Expression of the P85 Regulatory Unit of Phosphatidylinositol 3-Kinase and Triggers Severe Insulin Resistance in Skeletal Muscle

Abstract: The insulin resistance of normal pregnancy is necessary to divert fuels to the fetus to meet fetal growth demands and is mediated by placental hormones. We recently demonstrated that human placental GH (hPGH) can trigger severe insulin resistance in transgenic (TG) mice. In this study we sought to elucidate the cellular mechanisms by which hPGH interferes with insulin signaling in muscle in TG mice. Insulin-stimulated GLUT-4 translocation to the plasma membrane (PM) was reduced in the TG compared with wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
129
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(135 citation statements)
references
References 27 publications
4
129
0
2
Order By: Relevance
“…Recently, Barbour and colleagues (87,93) demonstrated that insulin resistance of pregnancy is likely due to increased expression of skeletal muscle p85 in response to increasing concentrations of human placental growth hor- mone. Furthermore, women remaining insulin resistant postpartum have been found to display higher levels of p85 in the muscle (94).…”
Section: Increased Expression Of P85〈mentioning
confidence: 99%
“…Recently, Barbour and colleagues (87,93) demonstrated that insulin resistance of pregnancy is likely due to increased expression of skeletal muscle p85 in response to increasing concentrations of human placental growth hor- mone. Furthermore, women remaining insulin resistant postpartum have been found to display higher levels of p85 in the muscle (94).…”
Section: Increased Expression Of P85〈mentioning
confidence: 99%
“…Recently, Barbour et al [15] demonstrated that the insulin resistance of pregnancy is likely to be due to Fig. 3 Correlation between the p85α:p110 ratio and glucose infusion rate (GIR) (a) and changes in PI 3-kinase activity and changes in GIR (b) in eight lean women.…”
Section: Discussionmentioning
confidence: 99%
“…PI 3-kinase activity was determined in 1-3 μl of the immunoprecipitate by thin layer chromatography, as described previously [15].…”
Section: Determination Of Irs-1-associated Pi 3-kinase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…As speculation, this regulation may lead to changes in PGH secretion in conditions associated with altered levels of hormones and adipokines such as in diabetic pregnancies. Thus, we selected hormones and adipokines, which are known to be closely related to fetal growth and adiposity, and tested their potential to act as PGH secretagauges: insulin as a potent stimulator of fetal growth and lipogenesis (15); IGF-1, which is related to increased birth size in diabetic pregnancies (16), and cortisol, also linked to fetal growth (17). Among the adipokines, we choose leptin, which is closely associated with fetal overgrowth (18) and reflects the mother's body fat mass (19), ghrelin, which, in low levels, is associated with increased insulin resistance and inversely related to birth weight (20), and visfatin, which is altered in gestational diabetes (21).…”
mentioning
confidence: 99%